Comparing knowledge, attitude, practice and stigma associated with SARS- COV-2 Infection among Healthcare students of Bangalore city: A cross sectional study - N K, Brunda; N, Sujatha; Kurre, Bhaskar (Indian Journal of Community Health, 2021)
Background: In 2020, a new global pandemic has emerged, caused by a new strain of Corona virus called SARS-CoV-2. A poor understanding of the disease among healthcare students may implicate in delayed treatment and rapid spread of infection and development of complications. Objectives: 1) To estimate the knowledge, attitude, practice and stigma associated with SARS- CoV-2 infection among healthcare students. 2) To estimate the association between socio-demographic determinants with knowledge, attitude, practice and stigma of SARS- CoV-2 infection among healthcare students. Methods: A web-based cross-sectional study was undertaken among 493 healthcare i.e., medical, nursing and allied sciences students, during 1st May to 20th May 2020, using a pre-designed and semi-structured questionnaire. Data was analyzed using Chi square test, t-test, one way Anova and Bonferroni test was used for assessing the association among the study variables. Results: The study revealed that, there were about 225(45.64%) medical, 165(33.46%) nursing and 103(20.89%) allied sciences students. Majority were females 349(70.79%), majority were Hindus 333(67.54%). Mean knowledge score of medical, nursing and allied sciences students were 15.66 (2.518), 14.16 (2.92) and 14.46 (3.11) respectively. Practice score was good among nursing than allied sciences students at ‘p’ (0.003). Conclusion: Even though the overall knowledge was less in our study participants, majority of them had followed good practices for preventing SARS- CoV-2 infection.